2005
DOI: 10.1111/j.1467-9442.2005.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Inflation Always and Everywhere a Monetary Phenomenon?*

Abstract: Using a sample of about 160 countries over the last 30 years, we test for the quantity theory relationship between money and inflation. When analysing the full sample of countries, we find a strong positive relation between long-run inflation and the money growth rate. The relation is not proportional, however. The strong link between inflation and money growth is almost wholly due to the presence of high-(or hyper-) inflation countries in the sample. The relationship between inflation and money growth for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(44 citation statements)
references
References 13 publications
6
37
0
1
Order By: Relevance
“…This result has corroborated the findings of Jalil, Tariq, and Bibi (2014) for Pakistani economy which discovered that debts financing in Pakistan had been passing through to increase in price level, which affirmed the plausibility of fiscal theory of price level in Pakistan. Also, the study confirmed the assertion of Grauwe and Polan (2005) that money does not matter in an economy which does not experience hyperinflation. Again, the result tilted towards the findings of Omanukwue (2010) on Nigerian economy which tested the plausibility of quantity theory of money and found that the relationship between money and inflation was weak.…”
Section: Cointegrationsupporting
confidence: 81%
“…This result has corroborated the findings of Jalil, Tariq, and Bibi (2014) for Pakistani economy which discovered that debts financing in Pakistan had been passing through to increase in price level, which affirmed the plausibility of fiscal theory of price level in Pakistan. Also, the study confirmed the assertion of Grauwe and Polan (2005) that money does not matter in an economy which does not experience hyperinflation. Again, the result tilted towards the findings of Omanukwue (2010) on Nigerian economy which tested the plausibility of quantity theory of money and found that the relationship between money and inflation was weak.…”
Section: Cointegrationsupporting
confidence: 81%
“…D'Agostino and others (2006) make the point that the predictability of macroeconomic variables in general may have been lowered as macroeconomic volatility declined during the great moderation. 42 In a related result, de Grauwe and Polan (2005) report that the relationship between money and longer-run inflation is the strongest in high-inflation countries. This suggests focusing any comparative analysis of competing models of inflation on a unified sample period, preferably a recent one to maximize the relevance of results for policy makers.…”
Section: B a Systematic Analysis Of The Information Content Of Moneymentioning
confidence: 90%
“…For example, Roffia and Zaghini (2007) show that, over a three-year horizon, in a panel of 15 industrialized countries starting in early 1970s, episodes of strong money growth are related to higher inflation only in about half of the 71 cases. De Grauwe and Polan (2005), looking at a large panel of about 160 countries since the 1970s find that the relationship between money and longer-run inflation is weak at best for low-inflation regions comparable to today's euro area. Gerlach andSvensson (2003, p.1669) find that the growth rate of nominal M3 adds little to the forecasting accuracy of an output-gap based model of euro-area inflation, which to them suggests "considerable doubt on its usefulness for policy purposes."…”
Section: A a Brief Survey Of The Empirical Literaturementioning
confidence: 99%
“…For example, Roffia and Zaghini (2007) and De Grauwe and Polan (2005) argue that the relationship between money and inflation across industrialized countries and time my be weaker than what is commonly thought. For the euro area, Gerlach and Svensson (2003) find that the growth rate of nominal M3 adds little to the forecasting accuracy of an output-gap based model of euro area inflation.…”
Section: Related Literaturementioning
confidence: 92%